2023
DOI: 10.3390/s23208609
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Based Machine Learning Model for Fast Diagnosis and Monitoring of Parkinson’s Disease

Maksim Belyaev,
Murugappan Murugappan,
Andrei Velichko
et al.

Abstract: This study presents the concept of a computationally efficient machine learning (ML) model for diagnosing and monitoring Parkinson’s disease (PD) using rest-state EEG signals (rs-EEG) from 20 PD subjects and 20 normal control (NC) subjects at a sampling rate of 128 Hz. Based on the comparative analysis of the effectiveness of entropy calculation methods, fuzzy entropy showed the best results in diagnosing and monitoring PD using rs-EEG, with classification accuracy (ARKF) of ~99.9%. The most important frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…The fact that FuzzyEn turned out to be more effective in classifying short (N = 300) time series than NNetEn confirmed the results of our work on the classification of EEG signals [1]. Moreover, experimental work [1,3] showed that FuzzyEn was the most effective compared to the other entropies, such as SampEn, SVDEn, and PermEn. However, individual pairs of time series can be better classified by NNetEn; this was also confirmed in the EEG experiment [1], where one channel performed better when using NNetEn as a feature.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The fact that FuzzyEn turned out to be more effective in classifying short (N = 300) time series than NNetEn confirmed the results of our work on the classification of EEG signals [1]. Moreover, experimental work [1,3] showed that FuzzyEn was the most effective compared to the other entropies, such as SampEn, SVDEn, and PermEn. However, individual pairs of time series can be better classified by NNetEn; this was also confirmed in the EEG experiment [1], where one channel performed better when using NNetEn as a feature.…”
Section: Discussionsupporting
confidence: 82%
“…The classification of time series based on entropy analysis and machine learning (ML) is a trending task in the study of nonlinear signals in the fields of finance, biology, and medicine, for example, in EEG classification in diagnosing Alzheimer's disease [1,2] and Parkinson's disease [3][4][5][6]. The creation of Brain-Computer Interfacing (BCI) [7] enables the classification of the movements of body parts according to EEG signals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations